Coronavirus Disease 2019–Associated Invasive Fungal Infection. (16th November 2021) - Baddley, John W; Thompson, George R; Chen, Sharon C -A; White, P Lewis; Johnson, Melissa D; Nguyen, M Hong; Schwartz, Ilan S; Spec, Andrej; Ostrosky-Zeichner, Luis; Jackson, Brendan R; Patterson, Thomas F; Pappas, Peter G
Abstract: Coronavirus disease 2019 (COVID-19) can become complicated by secondary invasive fungal infections (IFIs), stemming primarily from severe lung damage and immunologic deficits associated with the virus or immunomodulatory therapy. Other risk factors include poorly controlled diabetes, structural lung disease and/or other comorbidities, and fungal colonization. Opportunistic IFI following severe respiratory viral illness has been increasingly recognized, most notably with severe influenza. There have been many reports of fungal infections associated with COVID-19, initially predominated by pulmonary aspergillosis, but with recent emergence of mucormycosis, candidiasis, and endemic mycoses. These infections can be challenging to diagnose and are associated with poor outcomes. The reported incidence of IFI has varied, often related to heterogeneity in patient populations, surveillance protocols, and definitions used for classification of fungal infections. Herein, we review IFI complicating COVID-19 and address knowledge gaps related to epidemiology, diagnosis, and management of COVID-19–associated fungal infections.